Infrastructural facilities in primary health centre: A case study of Panchkula (Haryana) - Kapoor, Hitesh (2008)
Primary Health Care requires strong and continued political commitment at all levels of government, based upon the full understanding and support of the people. It is suggested that governments express their political will to attain health for all by making a continuing commitment of implement primary health care as an integral part of the national health system within overall socio-economic development, with the involvement of all sectors concerned to adopt enabling legislation where necessary and to stimulate, mobilise and sustain public interest and participation in the development of primary health care. - Reproduced.
Keywords: Health services - India - Haryana; Health services